ALGORITHMIC HALAL VISIBILITY: PRODUCING RELIGIOUS LEGITIMACY IN DIGITAL STREET-FOOD PLATFORMS - Diah Handayani; Rudad Ilaina; Yuyun Wahyu Izzati Surya; Sutinah Sutinah (J-MD Jurnal Manajemen Dakwah, 2026)
This study aims to examine how algorithmic aesthetics shape the production of halal-oriented digital spaces in street-food promotion across social media platforms and to explain how halal becomes visible, recognizable, and socially trusted within algorithmically mediated environments. Employing a qualitative approach, the research integrates virtual ethnography and Critical Discourse Analysis (CDA) to analyze 48 digital content items, 1,284 audience comments, 116 captions and metadata entries, 90 visual screenshots, and in-depth interviews with street-food vendors featured on Instagram, Facebook Reels, and YouTube. The findings reveal that halal no longer operates solely as a legal category verified through formal certification but is produced through the interaction of three interconnected dimensions: spatial practices, representations of space, and representational spaces. Within this process, visual cleanliness, transparency, ethical labor, and Islamic moral cues function as communicative resources through which audiences construct trust and recognize halal legitimacy. The study further demonstrates that platform logics, visual aesthetics, and algorithmic mechanisms influence which representations of halal achieve greater visibility and public recognition. This research is limited to a selected number of social media accounts and platforms within the Indonesian context and therefore may not fully capture variations across different cultural and technological settings. Practically, the findings provide insights for food entrepreneurs, digital content creators, and policymakers regarding the growing importance of digital visibility in shaping public trust and perceptions of halal authenticity. The originality of this study lies in the development of the concept of Algorithmic Halal Visibility, which explains how religious legitimacy is produced through the interaction of everyday practices, symbolic representations, audience participation, and platform infrastructures in contemporary digital societies.